Therapeutic Drug Monitoring (TDM) Implementation in Public Hospitals in Greece in 2003 and 2021: A Comparative Analysis of TDM Evolution over the Years - Gavriela Voulgaridou; Theodora Paraskeva; Georgia Ragia; Natalia Atzemian; Konstantina Portokallidou; George Kolios; Konstantinos Arvanitidis; Vangelis G. Manolopoulos (MDPI AG, 2023)
Therapeutic drug monitoring (TDM) is the clinical practice of measuring drug concentrations. TDM can be used to determine treatment efficacy and to prevent the occurrence or reduce the risk of drug-induced side effects, being, thus, a tool of personalized medicine. Drugs for which TDM is applied should have a narrow therapeutic range and exhibit both significant pharmacokinetic variability and a predefined target concentration range. The aim of our study was to assess the current status of TDM in Greek public hospitals and estimate its progress over the last 20 years. All Greek public hospitals were contacted to provide data and details on the clinical uptake of TDM in Greece for the years 2003 and 2021 through a structured questionnaire. Data from 113 out of 132 Greek hospitals were collected in 2003, whereas for 2021, we have collected data from 98 out of 122 hospitals. Among these, in 2003 and 2021, 64 and 51 hospitals, respectively, performed TDM. Antiepileptics and antibiotics were the most common drug categories monitored in both years. The total number of drug measurement assays decreased from 2003 to 2021 (153,313 ± 7794 vs. 90,065 ± 5698; p = 0.043). In direct comparisons between hospitals where TDM was performed both in 2003 and 2021 (n = 35), the mean number of measurements was found to decrease for most drugs, including carbamazepine (198.8 ± 46.6 vs. 46.6 ± 10.1, p < 0.001), phenytoin (253.6 ± 59 vs. 120 ± 34.3; p = 0.001), amikacin (147.3 ± 65.2 vs. 91.1 ± 71.4; p = 0.033), digoxin (783.2 ± 226.70 vs. 165.9 ± 28.9; p < 0.001), and theophylline (71.5 ± 28.7 vs. 11.9 ± 6.4; p = 0.004). Only for vancomycin, a significant increase in measurements was recorded (206.1 ± 96.1 vs. 789.1 ± 282.8; p = 0.012). In conclusion, our findings show that TDM clinical implementation is losing ground in Greek hospitals. Efforts and initiatives to reverse this trend are urgently needed.